The Unwanted - Peeva, Adela (Bulgaria, 2000)
In the South-Eastern part of Bulgaria, close to the border with Turkey, two communities have always lived together — the Bulgarians and the Turks. In the mid 80’s, in an attempt to resolve the ethnic problems that had been accumulating for years, the authorities forced about 1 million Turks to change their Turkish names into Bulgarian ones. The ones who did not accept Bulgarian names had to leave Bulgaria. Within a couple of months more than 350.000 people migrated to Turkey. Entire villages and regions were depopulated. Turkey at first accepted the immigrants, but then unexpectedly closed its borders. This resulted in thousands of divided families. “Unwanted” presents three of these.
Soros Documentary Fund
Soros Documentary Fund
Keywords: Documentary films